2016
DOI: 10.1111/anec.12357
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of QRS Fragmentation in Patients with Acute Myocardial Infarction: A Meta‐Analysis

Abstract: We searched PubMed, Embase, Web of Science, and Cochrane Library up to October 2015 for eligible studies. We selected studies with fQRS defined with 12-lead ECG during the index hospitalization of STEMI/NSTEMI. Primary outcomes were in-hospital and long-term cardiovascular events. In-hospital mortality was significantly higher in fQRS (+) group (99/733; 13.5%) compared to fQRS (-) group (47/1293; 3.6%) (OR 4.03 95% CI 1.81-8.94; P = 0.0006). Long-term mortality rate was higher in fQRS (+) group (89/473; 18.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
2
28
0
3
Order By: Relevance
“…As we have shown in our meta-analysis, and also in previous studies, the presence of fQRS is associated with more severe form of coronary atherosclerosis and left ventricular systolic dysfunction (Güngör et al, 2016). As we have shown in our meta-analysis, and also in previous studies, the presence of fQRS is associated with more severe form of coronary atherosclerosis and left ventricular systolic dysfunction (Güngör et al, 2016).…”
Section: Dear Editorsupporting
confidence: 86%
“…As we have shown in our meta-analysis, and also in previous studies, the presence of fQRS is associated with more severe form of coronary atherosclerosis and left ventricular systolic dysfunction (Güngör et al, 2016). As we have shown in our meta-analysis, and also in previous studies, the presence of fQRS is associated with more severe form of coronary atherosclerosis and left ventricular systolic dysfunction (Güngör et al, 2016).…”
Section: Dear Editorsupporting
confidence: 86%
“…Previous studies have demonstrated that ECGs might be used for risk stratification in patients who present with STEMI (Birnbaum & Sclarovsky, ; Nable & Brady, ). Several electrocardiographic parameters have been examined, including the magnitude of ST‐segment elevation, the T‐wave morphology, the presence of early repolarization, and fragmented QRS, on admission in patients with acute myocardial infarction (Atar & Birnbaum, ; Birnbaum et al, ; Güngör et al, ; Ozcan et al, ). Tomb‐ST is an electrocardiographic pattern of ST‐segment elevation in which the QRS complex, the ST segment, and the T wave merge to form a large upright monophasic deflection called a “tombstone” (Wimalaratna, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ECGs might be used for risk stratification in patients who present with STEMI (Birnbaum & Sclarovsky, 2001;Nable & Brady, 2009). Several electrocardiographic parameters have been examined, including the magnitude of ST-segment elevation, the T-wave morphology, the presence of early repolarization, and fragmented QRS, on admission in patients with acute myocardial infarction (Atar & Birnbaum, 2005;Güngör et al, 2016;Ozcan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Especially when occurring in the lateral territory fQRS has been noticed to increase not only the non-fatal cardiac events and long-term cardiovascular events but also mortality in patients with CAD (Jain et al, 2014; Gong and Li, 2016; Güngör et al, 2016). It is possible that fQRS could detect some subclinical regional left ventricle dysfunction in patients with CAD (Yan et al, 2012).…”
Section: Backgroundsmentioning
confidence: 99%
“…fQRS can also be associated with low LVEF. (Fares et al, 2013; Lorgis et al, 2014; Gong and Li, 2016; Güngör et al, 2016; Ma et al, 2016) and multi-vessel CAD in patients with STEMI (Ma et al, 2016) and NSTEMI (Güngör et al, 2016) which may explain the association with adverse prognosis. In silent MIs, which are problematic to discover in diabetics, women with unusual chest pain and in senile dementia, fQRS can be the only evidence of the ongoing event (Fares et al, 2013).…”
Section: Backgroundsmentioning
confidence: 99%